Stosunki polsko-amerykańskie po uzyskaniu przez Polskę członkostwa w Unii Europejskiej - Habowski, Mirosław (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2014)
The primary area of the Polish-American cooperation is security. Poland is the United State’s ally in NATO, which was reflected in its engagement in the war in Iraq and Afghanistan. Being interested in the traditional functions of NATO in the first place, particularly in those stemming from Art. 5 of the Washington Treaty, Poland treated the American postulates on globalising the Alliance’s functions with huge openness. When J. Kaczyński was in office, the Republic of Poland was striving to achieve bilateralization of mutual relations, even at the expense of NATO. Participation in the American programme of anti-missile defence system was supposed to serve that goal. Within a short period of time that concept collapsed. After B. Obama had been elected president of the USA, Poland’s significance for the US decreased even more.
Keywords: Polska; USA; bezpieczeństwo; tarcza antyrakietowa; współpraca wojskowa; NATO